2017
DOI: 10.1016/j.jare.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles profiling in Ceratonia siliqua (Carob bean) from Egypt and in response to roasting as analyzed via solid-phase microextraction coupled to chemometrics

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…According to Hanousek Čiča, the characterization of aroma compounds of carob pods macerates in hydroalcoholic base shows 27 components subdivided into 17 esters, four ketones, two acids and three alcohols, constituting of 70–85% of total aroma compounds [ 34 ]. Another study identified seven different volatile groups, with acids as the most abundant class (71%–77% in pods powder) [ 35 ]. Despite the extraction method, difference seems to be primarily due to ecological factors and to the extracted organ: pods with seeds or pods deseeded and to the type of investigated cultivars i.e., male, female or hermaphrodite [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Hanousek Čiča, the characterization of aroma compounds of carob pods macerates in hydroalcoholic base shows 27 components subdivided into 17 esters, four ketones, two acids and three alcohols, constituting of 70–85% of total aroma compounds [ 34 ]. Another study identified seven different volatile groups, with acids as the most abundant class (71%–77% in pods powder) [ 35 ]. Despite the extraction method, difference seems to be primarily due to ecological factors and to the extracted organ: pods with seeds or pods deseeded and to the type of investigated cultivars i.e., male, female or hermaphrodite [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The latter method was applied for the differentiation of LBG among other carbohydrate gums and gums mixtures [45] . Furthermore, Farag et al, studied the aroma profile of roasted and unroasted carob pods using solid-phase microextraction gas chromatography-mass spectrometry (SPME-GC-MS) analysis associated with chemometrics [46] . Also, capillary zone electrophoresis was combined with chemometrics for the classification of carob gum samples [47] .…”
Section: Introductionmentioning
confidence: 99%
“…Detected acids among others contribute not only to the total acidity of the samples but also to the overall flavor and aroma. Namely, Farag and El‐Kersh () detected short‐chain fatty acids like pentanoic acid (15%–25%) and hexanoic acid (20%) as the main components in carob pod volatiles. Several other less abundant acids were detected including pyruvic, isobutyric, butyric, heptanoic acid, octanoic, and benzoic acids.…”
Section: Discussionmentioning
confidence: 99%